Validasi Modul Elektronika Dasar Mengintegrasikan Creative Thinking Pada Materi Rangkaian Dioda dan Aplikasinya - Triani, Frima; Hufri, Hufri (Universitas Negeri Padang, 2020)
The low level of creative thinking of students in Indonesia is something that must be of concern, especially for the world of education. To emphasize understanding and develop creative thinking, students need to be facilitated with tools that support learning. One of them is the module that integrates creative thinking in it. The research carried out includes the type of Research and Development, namely the development of basic electronics modules integrating creative thinking in the diode circuit material and its applications. The design model used is the ADDIE model. This study aims to determine the validity of basic electronics modules integrating creative thinking in the diode circuit material and its applications. This value is obtained from a validity test questionnaire by experts. Based on the data analysis that has been done, the average value of module validation is 83.97%. Based on this value, it can be stated that the overall module components are already in the very valid category.